The dynamics of crude oil price movements : from price expectation perspectives - Lucy Kusnadi (2014)
The movement of crude oil price that was once relatively stable has exhibited huge volatility since the 2000s. Recently, crude oil price fluctuates sharply more than did it in the past whenever there are positive or negative economic shocks. Besides the traditional fundamental factors that are widely deemed driving the fluctuations of crude oil price, emerging factors, such as financialization of crude oil, have been found relevant to the price volatility. A substantial increase of open interest and transaction volume of crude oil futures appears to lead to escalating futures price and thus spot price through rational price expectation channel. By employing VECM, a cointegrating equation is constructed which exhibits the long-run positive correlation between spot and futures prices over the years in review. The results of Granger Causality Test show that the futures price and aggregate demand remains the two significant factors that predict the spot price movement. With such, the intensifying financialization of crude oil is expected to be a catalyst beyond economic fundamentals which further boosts and destabilizes the price of crude oil.